Laparoscopic supracervical hysterectomy versus endometrial ablation for women with heavy menstrual bleeding (HEALTH): a parallel-group, open-label, randomised controlled trial. Issue 10207 (19th October 2019) - Cooper, Kevin; Breeman, Suzanne; Scott, Neil W; Scotland, Graham; Clark, Justin; Hawe, Jed; Hawthorn, Robert; Phillips, Kevin; MacLennan, Graeme; Wileman, Samantha; McCormack, Kirsty; Hernández, Rodolfo; et al.
Summary: Background: Heavy menstrual bleeding affects 25% of women in the UK, many of whom require surgery to treat it. Hysterectomy is effective but has more complications than endometrial ablation, which is less invasive but ultimately leads to hysterectomy in 20% of women. We compared laparoscopic supracervical hysterectomy with endometrial ablation in women seeking surgical treatment for heavy menstrual bleeding. Methods: In this parallel-group, multicentre, open-label, randomised controlled trial in 31 hospitals in the UK, women younger than 50 years who were referred to a gynaecologist for surgical treatment of heavy menstrual bleeding and who were eligible for endometrial ablation were randomly allocated (1:1) to either laparoscopic supracervical hysterectomy or second generation endometrial ablation. Women were randomly assigned by either an interactive voice response telephone system or an internet-based application with a minimisation algorithm based on centre and age group (<40 years vs ≥40 years). Laparoscopic supracervical hysterectomy involves laparoscopic (keyhole) surgery to remove the upper part of the uterus (the body) containing the endometrium. Endometrial ablation aims to treat heavy menstrual bleeding by destroying the endometrium, which is responsible for heavy periods. The co-primary clinical outcomes were patient satisfaction and condition-specific quality of life, measured with the menorrhagia multi-attribute quality of life scale (MMAS), assessed at 15 months after randomisation. Our analysis was based on the intention-to-treat principle. The trial was registered with the ISRCTN registry, number ISRCTN49013893. Findings: Between May 21, 2014, and March 28, 2017, we enrolled and randomly assigned 660 women (330 in each group). 616 (93%) of 660 women were operated on within the study period, 588 (95%) of whom received the allocated procedure and 28 (5%) of whom had an alternative surgery. At 15 months after randomisation, more women allocated to laparoscopic supracervical hysterectomy were satisfied with their operation compared with those in the endometrial ablation group (270 [97%] of 278 women vs 244 [87%] of 280 women; adjusted percentage difference 9·8, 95% CI 5·1–14·5; adjusted odds ratio [OR] 2·53, 95% CI 1·83–3·48; p<0·0001). Women randomly assigned to laparoscopic supracervical hysterectomy were also more likely to have the best possible MMAS score of 100 than women assigned to endometrial ablation (180 [69%] of 262 women vs 146 [54%] of 268 women; adjusted percentage difference 13·3, 95% CI 3·8–22·8; adjusted OR 1·87, 95% CI 1·31–2·67; p=0·00058). 14 (5%) of 309 women in the laparoscopic supracervical hysterectomy group and 11 (4%) of 307 women in the endometrial ablation group had at least one serious adverse event (adjusted OR 1·30, 95% CI 0·56–3·02; p=0·54). Interpretation: Laparoscopic supracervical hysterectomy is superior to endometrial ablation in terms of clinical effectiveness and has a similar proportion of complications, but takes longer to perform and is associated with a longer recovery. Funding: UK National Institute for Health Research Health Technology Assessment Programme.